Competencias en redacción periodística que demandan los medios impresos de la provincia de El Oro - Maldonado Ramon, Marjorie Elizabeth (Machala, 2019)
This work is about the journalistic writing competences that the print media demand from the newly graduated Communication Graduates of the province of El Oro. As for the academic training of the communicator, the media require that a recent graduate have experience in the journalistic writing that is the competition that is used most professionally. In the methodological section, the technique of interviews with local, national and international journalists was used to publicize their point of view regarding journalistic writing skills. It is worth mentioning that an interview was applied to the only two Graduates in Communication of the Utmach, recently graduated, who work in print media in the locality, as is the case of the newspaper companies Diario Correo and Diario Opinion with the purpose of determining what demand the print media in the area of journalistic writing. Surveys were also carried out for students from Fifth to Eighth semester of the Utmach communication career, since as future Communication Graduates, they sought to know their criteria on the importance they give to the journalistic writing subject in this semester 2019-DI and how they envision their future labor field in print media. In a complementary way, the literature review technique was used in scientific articles indexed in high-impact journals, with the purpose of analyzing the communication experts' vision regarding the journalistic challenges demanded by today's society.
Este trabajo trata acerca de las competencias de redacción periodística que los medios impresos demandan de los Licenciados en Comunicación, recién titulados, de la provincia de El Oro. En cuanto a la formación académica del comunicador los medios exigen que un recién titulado tenga experiencia en la redacción periodística que es la competencia que más se emplea a nivel profesional. En el apartado metodológico se empleó la técnica de entrevistas a periodistas locales, nacionales e internacionales para dar a conocer su punto de vista en referente a las competencias de redacción periodística. Cabe mencionar que se aplicó una entrevista a las dos únicas Licenciadas en Comunicación de la Utmach, recién tituladas, que trabajan en medios impresos en la localidad, como es el caso de las empresas de medios Diario Correo y Diario Opinión con el propósito de determinar qué demandan los medios impresos en el área de redacción periodística. También se realizó encuestas a los estudiantes de Quinto a Octavo semestre de la carrera de comunicación de la Utmach, ya que como futuros Licenciados en Comunicación se buscó conocer su criterio sobre la importancia que le dan a la asignatura de redacción periodística en el presente semestre lectivo 2019-DI y cómo avizoran su futuro campo laboral en medios impresos. De forma complementaria se utilizó la técnica de la revisión bibliográfica en artículos científicos indexados en revistas de alto impacto, con el propósito de analizar la visión de los comunicólogos en torno a los desafíos periodísticos que exige la sociedad actual.
Keywords: MEDIO IMPRESO; REDACCION PERIODISTICA; COMPETENCIA